2012
DOI: 10.2147/bctt.s24976
|View full text |Cite
|
Sign up to set email alerts
|

New developments in the treatment of HER2-positive breast cancer

Abstract: Approximately 20%–30% of metastatic breast cancers show increased expression of the human epidermal growth factor receptor-2 (HER2) tyrosine kinase. Two HER2-specific therapies are currently approved for clinical treatment of patients with HER2-overexpressing metastatic breast cancer. Trastuzumab is a monoclonal antibody against HER2 and is approved for first-line treatment of HER2-positive metastatic breast cancer. Lapatinib is a small molecule dual inhibitor of epidermal growth factor receptor and HER2 tyros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 107 publications
0
11
0
Order By: Relevance
“…Hence, ARTN could utilize TWIST1-dependent expression of BCL-2 to mediate acquired trastuzumab resistance by promotion of a CSClike cell population in mammary carcinoma. Given herein that we have demonstrated the requirement of BCL-2 in the ARTNmediated increase in the CSC-like population in trastuzumabresistant cells, we postulate that BCL-2 may act as an ARTNdependent potential downstream target in a wide a range of mammary carcinoma subtypes including HER2-dependent mammary carcinoma (20). In this regard it is important to note that regardless of the prognostic value of BCL-2 expression (40 -42), it is the interactions among the various BCL-2 family member proteins (e.g.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Hence, ARTN could utilize TWIST1-dependent expression of BCL-2 to mediate acquired trastuzumab resistance by promotion of a CSClike cell population in mammary carcinoma. Given herein that we have demonstrated the requirement of BCL-2 in the ARTNmediated increase in the CSC-like population in trastuzumabresistant cells, we postulate that BCL-2 may act as an ARTNdependent potential downstream target in a wide a range of mammary carcinoma subtypes including HER2-dependent mammary carcinoma (20). In this regard it is important to note that regardless of the prognostic value of BCL-2 expression (40 -42), it is the interactions among the various BCL-2 family member proteins (e.g.…”
Section: Discussionmentioning
confidence: 78%
“…HER2-overexpressing cell lines possess a higher level of BCL-2 expression (19), and increased BCL-2 expression has been reported to contribute to the development of trastuzumab resistance (20). Previously, ARTN has also been demonstrated to regulate BCL-2 in mammary carcinoma (15,16) and enhance the CSC population in a BCL-2-dependent manner.…”
mentioning
confidence: 99%
“…On the other hand, the EGF100151 study estimated the effectiveness of lapatinib in combination with capecitabine in such a group of patients, prolonged median time to progression (TTP) for 8.4 months. Moreover, improvement of the overall response rate (22%) and clinical benefit rate (27%), without increase in serious toxic effects was achieved [16,34,35].…”
Section: The Significance Of Her2 Status In Breast Cancer Patients Qumentioning
confidence: 97%
“…Luis et al suggested that the IHC technique should be used as a screening test for HER2 status diagnosis, wherein patients with high expression of HER2 protein (IHC3+) are the major candidates for molecularly-targeted therapy. However, IHC2+ results must be confirmed by more sensitive in situ hybridization methods [34][35][36][37]. On the other hand, the EMILIA study also indicated the prolongation of PFS and OS time after treatment with trastuzumab emtansine (T-DM1) in primary breast cancer patients after acquired resistance to trastuzumab and taxanes.…”
Section: The Significance Of Fish Analysis In Qualification For Anti-mentioning
confidence: 99%
See 1 more Smart Citation